rút gọn biểu thức A=(x-2)^3-x (x+1 )(x-1)+6x(x-3) B=(x-2)(x^2+2x+4)(x+2)(x^2x+4)

Question

rút gọn biểu thức
A=(x-2)^3-x (x+1 )(x-1)+6x(x-3)
B=(x-2)(x^2+2x+4)(x+2)(x^2x+4)

in progress 0
Ben Gia 2 years 2020-11-03T10:03:24+00:00 2 Answers 139 views 0

Answers ( )

    0
    2020-11-03T10:04:51+00:00

    Đáp án:

     `A=-5x-8`

    `B=x^6-64`

    Giải thích các bước giải:

     `A=(x-2)^3-x(x+1)(x-1)+6x(x-3)`

    `A=x^3-6x^2+12x-8-x(x^2-1)+6x^2-18x`

    `A=x^3-6x-8-x^3+x`

    `A=-5x-8`

    `B=(x-2)(x^2+2x+4)(x+2)(x^2-2x+4)`

    `B=(x^3-8)(x^3+8)`

    `B=(x^3)^2-8^2`

    `B=x^6-64`

    0
    2020-11-03T10:05:00+00:00

    Đáp án:

     

    Giải thích các bước giải:

     A=$(x-2)^3-x.(x+1).(x-1)+6x.(x-3)$

      =$x^3-6x^2+12x-8-x.(x^2-1)+6x^2-18x$

    $=x^3-6x^2+12x-8-x^3+x+6x^2-18x$

    $=-5x-8$

    B=$(x-2).(x^2+2x+4).(x^2+2).(x^2-2x+4)$

    $=[(x-2).(x^2+2x+4)].[(x^2+2).(x^2-2x+4)]$

    $=(x^3-8).(x^3+8)$

    $=x^6-64$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )